Active ozone removal technologies for a safe indoor environment: A comprehensive review. (January 2021) - Namdari, Marzieh; Lee, Chang-Seo; Haghighat, Fariborz
Abstract: Ozone is a highly reactive gas and one of the critical air pollutants for both indoor and outdoor environments. The Occupational Safety and Health Administration (OSHA) determined that the permissible level of ozone is 100 ppb—for 8-h exposure at workplaces. Therefore, using an ozone removal technology can be crucial when outdoor ozone concentration is high and where active ozone emission sources exist. Activated carbon-based filters, catalytic decomposition, and photocatalytic decomposition are air treatment technologies that have been used for ozone removal. The catalytic decomposition approach showed higher efficiency and higher durability with no generation of considerable by-products, particularly manganese oxide (MnOx ) based catalysts, which can decompose ozone to oxygen at room temperature. The low cost, as well as high catalytic activity, are among the advantages of MnOx -based catalysts. High specific surface area, high density of oxygen vacancy, high reducibility, and low average oxidation state are desirable properties of the catalyst for ozone decomposition. Despite their excellent performance, their loss of activity in humid conditions challenges their widespread applications. This review presents the recent studies on ozone decomposition technologies, particularly MnOx -based catalysts performance and modification techniques used to improve their performance, and potential future research directions in this field.